Characteristics of water consumption by the population of industrial city - Koval V.V. (Medičnì Perspektivi, 2015)
The article presents the characteristics of water consumption by population of a modern industrial city. Results of the study show that the problem of drinking tap water is relevant for the residents of the industrial city. Methods of drinking tap water purification used by population of the industrial city at home in order to improve its quality were identified. It is found that a certain part of the population (5.7%), mostly middle-aged persons with secondary education, consume tap water without pre-treatment or are limited to boiling it before use (6.3%). Considerable part of the population of the industrial city for drinking and cooking every day uses additionaly purified water. Of them, 27.6% prefer additionaly purified pre-packed water, 16.1% of respondents use drinking water from water spill points. The results of the survey indicate that 4.5% of respondents for purification of tap water use intrahouse filters, 20.3% - local (domestic) filters.